Temperature-frequency dependence on electrical properties of EuCI3 based composites, thermal behaviors and preparation of poly(3-acetamido propyl acrylate) - Biryan, Fatih; Demirelli, Kadir (Taylor & Francis Ltd, 2018)
The 3-acetamido propyl acrylate [AcAPA] (monomer) was synthesized. The homopolymerization of AcAPA was carried by normal free radical polymerization procedure within tetrahydrofuran at 60 C-o using AIBN as the initiator. The poly(AcAPA) composites embedded europium(III)chloride (EuCI3) were prepared. Dependent of temperature and frequency on the dielectric characteristics were investigated in a frequency range starting from 100Hz to 20000Hz and in a temperature range from 243K to 333K. The results showed that the dielectric loss and dielectric constant increased, and the highest dielectric values were estimated in the case of poly(AcAPA) composites loaded EuCI3 and graphite as well. The FT-IR results indicated that the structural characterization of poly(AcAPA) is strongly affected by the incorporation of EuCI3. Thermal analysis results show that the thermal stability of the EuCI3-doped poly(AcAPA) composites has improved compared to the pure poly(AcAPA). The thermal property of composites has improved significantly due to an increasing in filler loadings showing that a good coordination exists between EuCI3 particles and poly(AcAPA). The dielectric constants of poly(AcAPA)/EuCI3 composites have significantly improved with comparatively low dielectric loss values, indicating that the composites can be considered as a crucial material for embedded capacitor applications. Electrically conducting graphite-based poly(AcAPA)/EuCI3 composites were prepared and the surface morphology of polymer composites were characterized by SEM micrographics. Also, the dc electrical conductivities of graphite-based poly(AcAPA)/EuCI3 were investigated.
Keywords: Electrical behaviors; poly(AcAPA); graphite; composites EuCI3 based; thermal behavior; Tg; activation energy